2020
DOI: 10.1016/j.transci.2020.102821
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent (immune) plasma treatment in a myelodysplastic COVID-19 patient with disseminated tuberculosis

Abstract: During the ongoing COVID-19 pandemic due to the SARS-CoV-2 virus of which evidence-based medical paradigms cannot be easily applied; difficult clinical decisions shall be required particularly in the 'difficult-to-treat' cases of high risk group with associated comorbidities. Convalescent immune plasma therapy is a promising option as a sort of 'rescue' treatment in COVID-19 immune syndrome, where miraculous antiviral drugs are not available yet. In this report, we aim to convey our experience of multi-task tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 11 publications
0
42
0
2
Order By: Relevance
“…This needs careful interpretation due to a wide overall 95% CI as well as due to studies with different designs. This evidence is supported by two large cohort studies conducted in Spain and South Africa, showing that the risks for PCR-con rmed COVID-19 diagnosis, hospitalization, Intensive Care Unit (ICU) admission, and death among HIVpositive persons receiving ART were greater in men compared to old age [42][43][44][45][46][47][48]. However, the risk for hospitalization varied by the nucleoside transcriptase inhibitor (NRTI) regimen and was lower in patients receiving TDF/FTC versus those receiving other regimens [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This needs careful interpretation due to a wide overall 95% CI as well as due to studies with different designs. This evidence is supported by two large cohort studies conducted in Spain and South Africa, showing that the risks for PCR-con rmed COVID-19 diagnosis, hospitalization, Intensive Care Unit (ICU) admission, and death among HIVpositive persons receiving ART were greater in men compared to old age [42][43][44][45][46][47][48]. However, the risk for hospitalization varied by the nucleoside transcriptase inhibitor (NRTI) regimen and was lower in patients receiving TDF/FTC versus those receiving other regimens [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 90%
“…Each article that met selection criteria was fundamentally assessed for Author/Country, Population/Study design, Exposures, Comparators, Treatments, TB occurrence and SARS/MERS/COVID-19 severity, recovery and mortality rate. [28][29][30][31], one case control study [32] and four case series [33][34][35][36] were conducted in China, two case series [37][38] were done in Singapore, one case series [39] and one case control study [40] were undertaken in Saudi Arabia, a case series [41] was conducted in Italy, one cohort study was done in South Africa [42] and another in the Philippines [43], one case study was conducted in the United State of America [44], other three case studies were found in Turkey [45], Hong Kong [46] and India [47] respectively.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each article that met selection criteria was fundamentally assessed for Author/Country, Population/Study design, Exposures, Comparators, Treatments, TB occurrence and SARS/MERS/COVID-19 severity, recovery and mortality rate. [28][29][30][31], one case control study [32] and four case series [33][34][35][36] were conducted in China, two case series [37][38] were done in Singapore, one case series [39] and one case control study [40] were undertaken in Saudi Arabia, a case series [41] was conducted in Italy, one cohort study was done in South Africa [42] and another in the Philippines [43], one case study was conducted in the United State of America [44], other three case studies were found in Turkey [45], Hong Kong [46] and India [47] respectively. Lastly, a retrospective cohort was undertaken in eight countries (Italy, Belgium, Brazil, France, Russia, Singapore, Spain, and Switzerland) [27].…”
Section: Search Resultsmentioning
confidence: 99%